Pyrexia in Pregnancy and its Maternal and Fetal Outcome - Shrestha, A; Bhattarai, S; Madhup, SK (Kathmandu University Medical Journal, 2023)
Background Contemporary obstetrics has witnessed improved maternal and fetal outcomes, owing to several advances. Any source of maternal hyperthermia that results in significant core temperature increase (> 38°C), could potentially affect the fetus. Fetus being an integral part of the feto-maternal unit and pregnancy involving numerous physiological changes and adaptations, pyrexia during the pregnancy affects both the mother and her fetus adversely.Objective To find the etiology and prevalence of fever in pregnancy and to know the effect of fever on maternal and fetal outcome.Method Pregnant ladies with fever > 38°C, presenting to Obstetrics and Gynecology, Department of Dhulikhel Hospital were enrolled in the study. A detailed clinical history, thorough general and physical examinations were done. All risk factors were asked and recorded including all baseline investigations and cases were followed up till delivery. Maternal and fetal outcomes were recorded. Data were recorded in Excel and calculated using SPSS 26.Result Eighty patients presented with complaints of fever were included in this study. The mean age of the patient was 25.49± 4.50 years. Out of 80 patients, 46 (57.50%) presented with fever in the third trimester. The most common etiology of fever being urinary tract infection in 21 (26%) cases followed by respiratory tract infection in 20 (25.1%) cases. Twenty two newborns had low birth weight among which 12 (15%) neonates had IUGR. About 14 (17.5%) neonates were admitted in NICU due to various complications and perinatal mortality was in 9 (11.25%) cases. The most common antepartum complication was preterm labor in 16 (20%) cases.Conclusion Fever in pregnancy is still a challenge to obstetrician and the society at large due its problems related to its prevention, diagnosis, management and its feto-maternal outcome. Hence, an evaluation of the effect and outcomes of fever in pregnancy, provides definite knowledge of clinical epidemiology, and facilitates optimum prioritization of efforts and resources.